Anaerobic Process. (1st October 2015) - Li, Wei‐Zun; Qian, Yang; Chang, Chein‐Chi; Ju, Meiting
Abstract : A review of the literature published in 2014 on the focus of Anaerobic Process. It is divided into the following sections. Pretreatment Organic waste multiple‐stage co‐digestion Process Methodology and Technology